Morphology of the coffee (Coffea arabica L.) in commerciaol plots. Nicaragua. - Blanco-Navarro, Moisés; Haggar, Jeremy; Moraga, Pedro; Madriz, Jazmín del Carmen; Pavón, Giovanny (Agronomía Mesoamericana, 2003)
The study was conducted in the Centro de Capacitacion y Servicio Regional Pacifico (Botanical Garden), located in the city of Masatepe, Nicaragua; in the period from June 2000 to February 2001. The main objective was to characterize each coffee plot, based on their agro-ecological aspects. Eight coffee plots already established in full production, with different planting distances, shade levels and varieties. The methodology applied considered five sites per plot and ten plants per site; recording the following variables: plant height, number of layers, branch length, number of leaves per branch and stalk diameter. There were differences among the coffee plots due to the planted variety, shade and agronomic practices. Recommendations of the agronomic practices for the coffee crop are given.